Foreign direct investment & corruption in Sub-Saharan Africa: An empirical analysis at the local level - Julian Donaubauer; Peter Kannen; Frauke Steglich (Kiel Institute for the World Economy (IfW), 2018)
Geocoding firm-level data and matching them to georeferenced household survey data, we are the first to analyze whether the presence of foreign investors is associated with changes in local corruption around foreign-owned production facilities in Sub-Saharan African countries. Applying an estimation strategy that explores the spatial and temporal variation in the data, we find that the presence of foreign firms increases bribery among people living nearby. We show this effect to work through two mechanisms, namely via increased economic activity and partly via norm transmission.
Keywords: D1; F21; F23; O12; 330; FDI; corruption; georeferenced data; Sub-Saharan Africa